Tasarım-Uygulama Kesitinde İç Mimarlık Proje Stüdyosu Deneyimi - Kutlu, Rana; ÖZBEK, DERYA ADIGÜZEL (My University, 2012)
Design studios play an important role in interior design education. The student's knowledge, skills, competencies aimed to increase in the design studios which each grade level are followed in common process in the design approach with blended with different expectations. In the context of the study, it is aimed to increase the students’ knowledge and skills of the both conceptual and practical in the three grade level project studio which are dealt with the holistic approach of the union of designimplementation. In addition to, it is provided a real implementation project ambient that is established in the relationship of designer-employer and participatory design. On the other side, the applicable project is determined in the jury reviews and the user exhibition identified the informal competition environment.
Keywords: Fiziksel Çevre Kontrolü; Diploma Projesi; Interior Architecture Project Studio; Interior Architecture Practice; Studio Experience; Interior Architecture Education